З історії проституції в Чернігові (середина XІX – початок XX ст.) - Рига, Д. (Сiверянський літопис, 2019)
У статті мова йде про історію проституції в Чернігові середини XІX – початку
XІX ст. Розглядаються питання становлення, функціонування будинків розпусти в
Чернігові в означений час. The second half of the XIX century becomes a period of rather intense development for
the city of Chernihiv. If in 1836 there were only 5885 inhabitants in the city, then in 60 years
there were already more than 27 thousand. During this time in the provincial center the number
of educational institutions, hotels, restaurants, the theater is being built. But the development
of Chernigov also gives rise to certain negative phenomena. One of them was prostitution,
which in 1844, under the orders of Nicholas II, was legalized throughout the entire Russian
Empire. And this is not due to the attachment of the Emperor to the prostitutes. It simply
became obvious that repressive measures would not overcome prostitution. They could not be
destroyed by either Queen Anna Ioannovna, nor the daughter of Peter the Great, Empress
Elizabeth, nor Catherine II, who in 1763 ordered to send all the prostitutes to Siberia. Were
needed other, already tested in European countries methods. So, in 1844, rules were issued for
those who kept the houses of debauchery and for themselves prostitutes. It should be noted
that they acted until the October Revolution itself. Under the rules (so-called those rules), the
right to register prostitutes entirely relied on the police. And often, on the basis of inaccurate
information, unmarried women received a «yellow ticket», that is, a proxy certificate, and
along with it - undeserved shameful reputation. In tsarist Russia, there were two forms of prostitution: officially recognized as legal and secret. The first was under the control of the state and was subject to accounting, the other
was creative and amateur. According to the existing rules, to cease to be considered a prostitute and to be free from police surveillance was possible only in four cases: 1. After reaching a certain age. 2. In the case of marriage. 3. At will, but only after a lengthy police check. 4. For a «surety» of a venerable and trustworthy person. There is information that in 1865 in the provincial center there were 18 official prostitutes, in respect of which medical control was carried out. But how many existed at that time in the city of houses of depravity is unknown.